The Effect of Liquidity on the Financial Performance of Companies in the Property, Real Estate and Building Construction Sectors Listed on the Indonesia Stock Exchange in 2023 - Sanga, Marianus Hendrilensio; Situmorang, Resvina; Seik, Merlinda Friday; Bangngu, Sani Alesya; Taus, Stefani Petriana Welhelmina (CV. Get Press Indonesia, 2025)
The property and real estate sector requires large investments and long business cycles, which requires developers to have solid financial strategies and adequate liquidity. However, the relationship between liquidity and financial performance is still debated, as excess liquidity can indicate inefficiencies. Purpose: analyze the effect of liquidity on financial performance in property and real estate companies listed on the Indonesia Stock Exchange. Methods: A quantitative approach with a descriptive and causal design to measure the relationship between the liquidity and financial performance of property and real estate companies. Secondary data is obtained from the annual financial statements of companies listed on the IDX in 2023, with sampling using a census involving all companies in this sector. Results: The Current Ratio has a significant negative effect on ROA while the Quick Ratio has no effect on ROA. Meanwhile, F-Statistic value shows that liquidity has no effect on financial performance. Implications: The importance of balanced liquidity management to support the profitability and efficiency of the company's operations. Conclusion: Adequate liquidity needs to be optimized without sacrificing the potential for productive investment.